Language Error Analysis on The Banner Nameplate in Magetan Regency - Dinda Ayu Saputri; Kodrat Eko Putro Setiawan (AKSIS: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
This study aims to explain Indonesian language errors on signboards and banners in Magetan. The problem in this study is the mistake of using Indonesian on nameplate and banners in Magetan. The method used in the compilation of data uses a qualitative descriptive method of phenomenology. The data source in this study is a photo document that results from monitoring the use of Indonesian on signs and banners in the city of Magetan. For data retrieval techniques in this research using sampling snowball. The focus in Indonesian language error research on signboards and banners is on spelling, use of inappropriate sentences and foreign words.